2008
DOI: 10.3138/physio/60/1/10
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Gait Speed in Patients after Hip Fracture

Abstract: Impairments (summed lower extremity strength) and risk factors (perception of general health and balance confidence) are important predictors of gait speed in elders after hip fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(22 citation statements)
references
References 50 publications
0
21
0
1
Order By: Relevance
“…Muir, Kiel, Hannan, Magaziner, and Rubin () noted that balance‐related dynamic parameters are related to fall and fracture history in older adults. Mangione, Craik, Lopopolo, Tomlinson, and Brenneman () reported that muscular strength and gait speed are crucial predictors of hip fracture in older adults. Therefore, the biological phenotype of frailty is considered an effective predictor of fracture risk in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Muir, Kiel, Hannan, Magaziner, and Rubin () noted that balance‐related dynamic parameters are related to fall and fracture history in older adults. Mangione, Craik, Lopopolo, Tomlinson, and Brenneman () reported that muscular strength and gait speed are crucial predictors of hip fracture in older adults. Therefore, the biological phenotype of frailty is considered an effective predictor of fracture risk in older adults.…”
Section: Discussionmentioning
confidence: 99%
“…Gait speed will be calculated from the motion capture trials as a valid and reliable measure of physical performance during gait, commonly reported in the literature 93…”
Section: Methods and Analysismentioning
confidence: 99%
“…Before data collection, leg lengths were measured manually with the patient in a standing position, in centimeters, from the greater trochanter to the floor below the lateral malleolus separately for the left and the right limbs. The participants were asked to perform 3 acclimation trials to reduce the learning effect similar to previous work [32]. The temporospatial parameters that were collected included stride length, step width, double support and single support times, and center of mass displacement.…”
Section: Methodsmentioning
confidence: 99%